"From a chef's perspective or what I can sell on the menu?" Exploring culinary professionals' attitudes toward specialty beef production and barriers to adoption. Issue 8 (14th September 2021) - Leggett, Kailie; McCann, Roslynn; Brunson, Mark; Miller, Brett Alan; MacAdam, Jennifer
ABSTRACT: This research aims to understand the attitudes and values of culinary 'innovators' already working with 'local' or 'grass-fed/finished' beef. Semi-structured interviews were conducted with specialty chefs and butchers in the Rocky Mountain Region based on the hypothesis that they operate as opinion leaders and understand that the benefits of, and barriers to, implementation of their current meat program is crucial for successfully introducing new products, such as Rocky Mountain Legume-Finished beef. Interviews revealed that professionals struggle with being 'conscientious' and 'sustainable' while still providing a consistent product for their customers. Although a few chefs spoke of setting 'hard limits' and 'high standards' for products, this did not emerge as a financial reality for other chefs or customers. In order for alternative sources of beef to be truly viable, beef production must address both environmental and economic concerns, while providing a consistent product in terms of taste and quality. Understanding the concerns of culinary professionals allows alternative ranching and agricultural production methods to be tailored as a viable for beef producers.